Yoga in Communist Poland: A Case Study of Tadeusz Pasek's Teaching (1960-89) - Kozłowiec, Iwona (Religions of South Asia, 2024)
This article explores the popularization of yoga by Tadeusz Pasek (1925-2011). His characterization of yoga as "relaxation and concentration exercises" - cwirki - allowed practices derived from yoga to gain popularity in communist Poland. Classes were officially taught through the centres of the Society for the Propagation of Physical Culture (TKKF), a state institution funded by the communist authorities. Details of these classes were published in 1973 by the State Medical Publishing House (PZWL) in Theory and Methodology of Relaxation and Concentration Exercises. Pasek created a system of instructor training and certification within the framework of the TKKF, coordinated on a national level. He innovated model "calming centres", combining TKKF structures within state-run housing cooperatives, functioning as yoga studios, community centres, and venues for psychiatric rehabilitation after in-patient treatment. Pasek introduced relaxation and concentration exercises for the rehabilitation of patients with neurotic disorders. Consequently, yoga practices, smuggled under the official name of relaxation and concentration exercises, entered academic circles of scientists and doctors, and also popular culture. Although its popularity waned as more yoga schools established themselves in Poland after 1989, Pasek's innovation of culturally embedding the practices established a foundation for the development of many yoga traditions in post-communist Poland.